Patients' acceptance of placebo antibiotics in Japan: a prescription for antimicrobial resistance - Atsushi Ito; Yuichi Watanabe; Takashi Okumura (Taylor & Francis Group, 2022)
Background The generalized use of antibiotics has led to the emergence of bacteria which are resistant to antimicrobial agents. This stems in part from the patient's tendencies to seek antibiotics for diseases when not necessary. Hence, this article investigated patient acceptance of prescribing placebos as a substitute for unnecessary antibiotics in Japan, where physicians are under severe time constraints and are unable to offer explanations and persuade patients who demand unnecessary antibiotics prescription. Methods A web-based questionnaire was administered to assess patients' acceptance of the placebo treatment under informed consent. One thousand participants representing all genders and age-class were randomly selected from the online panel of a web-survey company. Results The results showed that 67.9% of the participants were "satisfied" to receive such treatments, whereas 20.6% indicated acceptance of the prescription but without satisfaction. In total, 88.5% of the participants accepted the prescription of placebo, a result consistent with that of a preceding study on placebo treatments conducted in the United States. In the survey, tone of persuasion did not affect the patients' attitudes; however, patients who were loyal to their physicians exhibited lower refusal rates. Conclusion The survey results showed that the prescription of "ethical placebos" could be an acceptable option for the patients in Japan. For ethical concerns, an additional literature survey was conducted and the result suggested that such a radical treatment option could be justified, provided that the prescription benefits patients and informed consent is properly obtained. Albeit it is impractical to use, because of ethical and operational concerns, it would be worth further investigation to ensure diversity in the countermeasures for antimicrobial resistance, a major public health threat nowadays.